PENINGKATAN PRESTASI BELAJAR IPAS SISWA TENTANG PERUBAHAN WUJUD BENDA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DI KELAS IV SD GMIT KUANFATU KABUPATEN TTS - Mala, Rambu Bauru; Hali, Antonius Suban; Koroh, Taty R. (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The method used in this study is classroom action research. The subjects in this study were 15 fourth grade students of Gmit Kuanfatu Elementary School. The research instruments used were test questions and observation sheets. The data analysis technique of this study was descriptive analysis by calculating the value of individual absorption capacity, classical learning completeness, and percentage of classical absorption capacity. The results of the study indicate that the application of the STAD type Cooperative learning model can improve the learning achievement of fourth grade students of Gmit Kuanfatu Elementary School. This can be seen from the results of student activities and tests in the first cycle with an absorption percentage of 58% and learning completion of 15%, and in the second cycle it increased with an absorption percentage of 84.33% and learning completion of 100%. Some of the obstacles found in the implementation of this model include student activities in group activities that have not shown good cooperation, there are still members who are less active, and there are still students who have difficulty working on questions but are still passive.